Enhanced mechanical properties of poly (vinyl alcohol)/boron phosphate nanocomposites - Ugraskan, Volkan; Sazci, Oguler; Hazar Yoruc, Afife Binnaz (SAGE PUBLICATIONS INC, 2021)
In the present study, the effects of partially water-soluble nanoscaled boron phosphate (BPO4) on the mechanical properties of poly (vinyl alcohol) (PVA) plasticised with ethylene glycol films were investigated for the first time. Firstly, BPO4 was synthesised at 500 degrees C using boric acid and phosphoric acid as precursors. Then, nanoscaled BPO4 was obtained by the ultrasonic homogenisation method. Finally, PVA/BPO4 composite films were prepared by the solvent casting method with different BPO4 weight ratios. As a result of mechanical studies of the composites, it was found that the tensile strength of pristine PVA was enhanced from 19.06 to 26.42 MPa with the addition of nanoscaled BPO4. Furthermore, the tensile moduli of the composites reached their maximum at 4.56 GPa for the composite with 7% BPO4 by weight. This indicates that BPO4 is a promising material as an additive for low-cost composite films with high mechanical performances.
Keywords: Poly(vinyl alcohol); boron phosphate; nanocomposites; films; thermoplastics; inorganic materials; mechanical properties; characterisation; Materials Science; Polymer Science